Pentingnya Pendidikan Karakter - Stephanus Ngamanken (Bina Nusantara University, 2014)
A study about character building was conducted to better understand the impact of character building for individual, family and community. This study used grounded research method. Individuals who have good or bad behaviors are affected by past experience in relation to the character building they received. A happy family or a broken-home family is also influenced by past experience of each member of the family. Moreover, the success or failure of a social organization in the society, in this case was a country, is also determined by the character building from the members of the organization. Finally, study concluded that character building is very important in achieving the happiness of individuals, family and society/country.